Ion Effects on Vanadium Transport in Nafion Membranes for Vanadium Redox Flow Batteries. Issue 13 (1st January 2017) - Lawton, Jamie S.; Jones, Amanda M.; Tang, Zhijiang; Lindsey, Melanie; Zawodzinski, Thomas
Abstract : Vanadium diffusion through Nafion membranes was investigated under conditions applicable to vanadium redox flow batteries (VRFBs). In this case, we examine the effects of interdiffusion of VO 2+ with protons, V 3+ and VO2 + by a 'cross-diffusion' experiment in which VO 2+ and the other ion diffuse from opposite sides of the membrane. Vanadium concentrations in reservoirs designed to flow solution over both sides of the membrane were monitored using UV/vis and EPR spectroscopies. The permeability of each ion was determined and diffusion coefficients determined from permeability and measurements of ion uptake by the membrane. The VO 2+ permeability is highest when H + is the only ion on the counter side, and decreases in the following order: H + > VO2 + > V 3+ .